A New, Simple and Versatile Strategy for the Synthesis of Short Segments of Zigzag‐Type Carbon Nanotubes. Issue 9 (27th January 2016) - André, Etienne; Boutonnet, Baptiste; Charles, Pauline; Martini, Cyril; Aguiar‐Hualde, Juan‐Manuel; Latil, Sylvain; Guérineau, Vincent; Hammad, Karim; Ray, Priyanka; Guillot, Régis; Huc, Vincent
Abstract: Short segments of zigzag single‐walled carbon nanotubes (SWCNTs) were obtained from a calixarene scaffold by using a completely new, simple and expedited strategy that allowed fine‐tuning of their diameters. This new approach also allows for functionalised short segments of zigzag SWCNTs to be obtained; a prerequisite towards their lengthening. These new SWCNT short segments/calixarene composites show interesting behaviour in solution. DFT analysis of these new compounds also suggests interesting photophysical behaviour. Along with the synthesis of various SWCNTs segments, this approach also constitutes a powerful tool for the construction of new, radially oriented π systems. Abstract : Cone‐shaped scaffolds : A simple approach is described for the synthesis of short segments of zigzag carbon nanotubes. A calix[4]arene locked in the cone conformation is used as a scaffold for the construction of diameter‐defined cyclo( m ‐phenylene), that is, a short segment of a (12, 0) zigzag carbon nanotube (see figure).